2021
DOI: 10.3390/molecules26165011
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Ability of Apocynin Loaded Nanoparticles (APO-NPs) as NADPH Oxidase (NOX)-Mediated ROS Modulator for Hydrogen Peroxide-Induced Oxidative Neuronal Injuries

Abstract: Apocynin (APO) is a known multi-enzymatic complexed compound, employed as a viable NADPH oxidase (NOX) inhibitor, extensively used in both traditional and modern-day therapeutic strategies to combat neuronal disorders. However, its therapeutic efficacy is limited by lower solubility and lesser bioavailability; thus, a suitable nanocarrier system to overcome such limitations is needed. The present study is designed to fabricate APO-loaded polymeric nanoparticles (APO-NPs) to enhance its therapeutic efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous results using apocynin also support our results in terms of the scavenging activity, confirming the better quenching of nitrite ions in the samples. Therefore, from the collective results, it can be concluded that cumulatively the APO-NPs showed a slightly better inhibition ability in comparison to APO alone [11]. The findings of this study demonstrate for the first time that apocynin treatments provide neuroprotection [9]…”
Section: No Analysismentioning
confidence: 59%
See 1 more Smart Citation
“…Previous results using apocynin also support our results in terms of the scavenging activity, confirming the better quenching of nitrite ions in the samples. Therefore, from the collective results, it can be concluded that cumulatively the APO-NPs showed a slightly better inhibition ability in comparison to APO alone [11]. The findings of this study demonstrate for the first time that apocynin treatments provide neuroprotection [9]…”
Section: No Analysismentioning
confidence: 59%
“…Further, a previous study showed that the intraperitoneal administration of apocynin specifically inhibits the assembly of NOX subunits (by inhibiting the translocation of the p47phox subunit from cytosol to plasma membranes) and prevented secondary BBB damage in a rat model (4 h post-blast) by restoring the dislodged tight junction proteins from the endothelial capillaries [10]. However, its therapeutic efficacy is limited by its lower solubility and bioavailability; thus, a suitable nanocarrier system to overcome such limitations is needed [11]. Drug delivery to the brain is becoming more and more important but is severely restricted by the blood-brain barrier, which severely restricts the therapy of many neurological diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review by Hembram et al (2018) , choosing AgNPs over AuNPs has been highlighted at in vivo level and can be supported by the reason of choosing Eco-friendly synthesis of AgNPs which has gained a vast recognition over globe not only because of their effectivity but also due to the efficacy ( Srivastava et al, 2018 ). Utilising the organic plant extracts in treating diseases specifically cancer is highly required considering no damage to the healthy cells which are surrounding in the tumor microenvironment ( Srivastava et al, 2018 ; Singh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%